2007
DOI: 10.1016/j.biopsycho.2006.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac vagal regulation differentiates among children at risk for behavior problems

Abstract: A sample of 335 five-year-old children participating in an ongoing longitudinal study was the focus of a study on the effects of emotional and behavioral challenge on cardiac activity in children with different patterns of early childhood behavior problems. The children were placed in one of three behavior problem groups (low behavior problems, risk for externalizing problems, risk for mixed externalizing/internalizing problems) based on their scores on the Child Behavior Checklist for 4-18 year-olds (Achenbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
330
7
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(370 citation statements)
references
References 59 publications
(64 reference statements)
32
330
7
1
Order By: Relevance
“…We did not fi nd evidence for the hypothesis that adolescents with and without mental health problems would differ in their physiological reaction to the stressor (e.g., Calkins et al, 2007;Rottenberg et al, 2005). However, we found an indirect effect via secure base behaviour.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…We did not fi nd evidence for the hypothesis that adolescents with and without mental health problems would differ in their physiological reaction to the stressor (e.g., Calkins et al, 2007;Rottenberg et al, 2005). However, we found an indirect effect via secure base behaviour.…”
Section: Discussioncontrasting
confidence: 92%
“…An explanation for the non-signifi cant relation between psychopathology and physiological reactivity might be the heterogeneity of the type of psychopathology in the clinical group. Unfortunately, the small sample size limited the statistical power to differentiate between adolescents with internalizing and externalizing problems (Calkins et al, 2007;Dietrich et al, 2007). Another explanation might be that other factors moderate the relation between psychopathology and physiological reactivity, such as environmental stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Moreover, comorbid internalizing and externalizing symptoms predict greater RSA withdrawal to emotion evocation than either internalizing or externalizing symptoms alone (Calkins, Graziano, & Keane, 2007;Pang & Beauchaine, 2013). In contrast, high RSA is associated with resilience among children who are exposed to adversity.…”
Section: Emotion Dysregulation and Youth Psychopathologymentioning
confidence: 99%
“…It is a selfreport questionnaire with eight syndrome subscales (Anxious/ Depressed, Withdrawn/Depressed, Somatic Complaints, Social Problems, Thought Problems, Attention Problems, Rule-Breaking Behavior, and Aggressive Behavior) which are related to screening emotional and behavioral problems across multiple cultures [12,13]. Although no normative Italian data on the most recent YSR are available to date, the psychometric properties of the previous YSR [14] version have been investigated recently in a study conducted in Italy, that showed the good validity and reliability of this test on the Italian population [15].…”
Section: Psychological Assessmentmentioning
confidence: 99%